Mutations in lysX as the new and reliable markers for tuberculosis Beijing and modern Beijing strains. (March 2016) - Zhao, Li-li; Xiao, Tong-yang; Sun, Qing; Liu, Hai-can; Zhao, Xiu-qin; Jiang, Yi; Li, Gui-lian; Zeng, Chun-yan; Wan, Kang-lin
Summary: Genotyping results and DNA sequencing analysis of 235 Mycobacterium tuberculosis ( M. tuberculosis ) isolates from China indicated that mutations at codon 995 (Pro CCG to Pro CCA) and 701 (Ile ATT to Thr ACT) in lysX gene (Rv1640c), are specific markers for Beijing and modern Beijing strains, respectively. This observation was also confirmed by 24 genomes of M. tuberculosis strains from other countries. Moreover, a simple and fast multiplex allele-specific PCR (MAS-PCR) method for detecting mutations at codon 995 and 701 in lysX has been established and used to screen 235 DNA samples obtained from M. tuberculosis isolates. In all cases, Beijing and modern Beijing strains were identified correctly.